NIMG-42. DURABLE OVERALL RESPONSE RATE (ORR) TARGETS FOR RECURRENT GLIOBLASTOMA (RGBM) CLINICAL TRIALS BASED ON THE HISTORIC ASSOCIATION BETWEEN ORR AND MEDIAN OVERALL SURVIVAL (MOS). (14th November 2022) - Ellingson, Benjamin; Wen, Patrick Y; Chang, Susan; van den Bent, Martin; Vogelbaum, Michael; Li, Gang; Li, Shanpeng; Kim, Jiyoon; Youssef, Gilbert; Wick, Wolfgang; Lassman, Andrew; Gilbert, Mark; et al.
Abstract: Durable overall response rate (ORR) remains a meaningful endpoint in recurrent GBM; however, the target ORR for single arm recurrent GBM trials has not been based on historic information or tied to patient outcomes. The current study reviewed past trials in recurrent GBM in order to judiciously define target ORRs for use in recurrent GBM trials. After reviewing 69 treatment arms comprising 4, 971 patients, ORR was 6.1%[95% CI 4.23; 8.76%] for cytotoxic chemotherapies (ORR=7.59% for CCNU, 7.57% for TMZ, 0.64% for CPT-11, and 5.32% for other agents), 3.37% for biologic agents, 7.97% for immunotherapies (select trials), and 26.8% for anti-angiogenic agents. ORRs were significantly correlated with median overall survival (mOS) across chemotherapy ( R 2 =0.4078, P< 0.0001 ), biologics ( R 2 =0.4003, P=0.0003 ), and immunotherapy trials ( R 2 =0.8994, P< 0.0001 ), but not anti-angiogenic agents ( R 2 =0, P=0.8937 ). Pooling data from chemotherapy, biologics, and immunotherapy trials, a meta-analysis indicated a strong correlation between ORR and mOS ( R 2 =0.3164, P< 0.0001; mOS[weeks]=0.6xORR+28.9 ), suggesting an ORR >20% results in an mOS of > 40.9 weeks, which is double the survival estimate of a treatment with ORR=0% and ≥ 2 months longer than treatments with ORR=5%. Assuming an ineffective therapy (control) has ORR=5%, a trial of 32 patients with a target ORR=20% leads to the 95% confidence interval higher than the control group. We conclude that single arm phase II studies in recurrent GBM with ≥ 32 patients should have a target ORR ≥ 20%. This was associated with a median OS of approximately 1 year. Importantly, durability of response should also be considered and was not assessed in the current meta-analysis.